TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

PestCoCa: Domain generalizable stored-grain pest detection via contrastive causal intervention representation - Jida Tian; Chuanyang Ma; Jiangtao Li; Muyi Sun; Huiling Zhou (Journal of Stored Products Research, 2026)

A successful NaCl reduction strategy: Using spent hen meat hydrolysates to improve the sensory and in vitro digestion properties of sodium-reduced Cantonese sausage - Ruixia Chen; Fidel Toldrá; Junyi Xiang; Huiling Yan; Weizheng Sun; Xiao-Chen Liu (Meat Science, 2026)

Arid–period floods and human adaptation promoted agricultural prosperity in the Neolithic heartland of the Middle Yellow River - Mengjing Li; Lin Chen; Yongxiu Lu; Rui Yang; Zili Wang; Huiling Sun; Aifeng Zhou (CATENA, 2026)

Sea-breeze and gust front influences on supercell evolution: Observational and numerical insights - Min Sun; Jianhua Dai; Huiling Yuan; Jianming Xu; Haojun Chen; Jiakai Zhu (Atmospheric Research, 2026)

Shaking table tests and seismic response mechanisms of group pile foundations for nuclear power plants - Wenfu He; Haonan Zhan; Feiyu Liu; Dean Sun; Huiling Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Molecular Basis of Biostimulant-enhanced Recovery from Late-spring Frost in Vitis Vinifera: A Transcriptomic Dissection - Chaoyue Feng; Xi Chen; Xinyi Luo; Huiyu Zhu; Huiling Ma; Xiaojun Liu; Yulong Li; Quan Sun; Rui Wang; Yaqi Wang (Journal of Plant Growth Regulation, 2026)

Evaluating the synergistic effects of anisaldehyde and three other widely recognized mosquito-attracting agents in urban parks - Yunchuan He; Hongyan Lyu; Bin Sun; Huiling Hao (International Journal of Tropical Insect Science, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Research and application of CMA numerical weather prediction in meteorological support for the Beijing Winter Olympics (2022) - Guo Deng; Xueshun Shen; Huiling Yuan; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Mingxuan Chen; Jianjie Wang; et al. (Science China Earth Sciences, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

Assessing the effect of composted cyclosporin A fermentation residue as organic fertilizer: Focus on soil fertility and antibiotic resistance - Dong Wang; Xiang Chen; Xiaofen Li; Qingwen Zhang; Jiaqi Hou; Yuefei Li; Beidou Xi; Zhihao Sun; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Journal of Environmental Sciences, 2025)

Insights into the impacts of diverse electron acceptors on perfluorooctanoic acid and perfluorooctane sulphonic acid removal in sediment - Huiling Sun; Liwei Zhang; Junfan Yao; Jiaqi Zhang; Tianyu Wang; Guangzhou Yu; Yan Kang; Haoqin Ma; Shaoping Kuang; Zizhang Guo; Xiaohan Jiang (Journal of Environmental Chemical Engineering, 2025)

Comparison of hailfall and nonhailfall clouds in a severe storm: Observations and mesoscale simulations - Huiling Yang; Yue Sun; Wenqing Wang; Yong Zeng; Shujing Shen; Han Yao; Liang Feng; Hui Xiao (Atmospheric Research, 2025)

Large-scale identification and association analysis of wheat grain weight genes using rice orthologs - Wensha Zhao; Shusong Zheng; Aoyan Zhang; Meng Yuan; Pengbo Song; Kefeng Song; Yueyue Li; Yuanhang Xing; Huiling Zhao; Jianqing Niu; Jianhui Wu; Hong-Qing Ling; et al. (Theoretical and Applied Genetics, 2025)

Molecular mechanism of the crosstalk between glucocorticoid receptor (GR) and hypoxia-inducible factor 3α (HIF-3α) pathways - Meina Zhang; Yang Guo; Xiaotong Diao; Mengqi Guo; Huiling Teng; Xiangnan Sun; Jingjing Zhuang; Chun Song; Xiangyang Xie; Dalei Wu (Marine Life Science & Technology, 2025)

Atomic-level defect engineering enables hollow ternary molybdenum phosphoselenide nanospheres for enhanced sodium-ion storage - Yao Guo; Yangjie Liu; Lihong Xu; Mujtaba Aminu Muhammad; Huiling Fang; Jiaqi Yu; Mengyao Tu; Xiang Hu; Chuan-Fu Sun; Zhenhai Wen (Chemical Engineering Journal, 2025)

Decoding the fate of antibiotic resistance genes in soil with the application of thermally treated gentamicin mycelial residues - Dong Wang; Qingwen Zhang; Zhihao Sun; Yuefei Li; Xiaomei Xie; Shuaishuai Xin; Guocheng Liu; Huiling Liu; Yanjun Xin (Bioresource Technology Reports, 2025)

Available phosphorus levels modulate growth performance, serum indices, metabolome, rumen fermentation, and microorganism in Hu lambs - Shijia Pan; Jifu Zou; Huiling Mao; Zhihong Hu; Shijie Sun; Wenxuan Wu; Jinyong Yang; Zhigao An; Chong Wang (Animal Feed Science and Technology, 2025)

Key functional guilds with high trophic level organisms in soil are vital contributors to greenhouse gas emissions from cropland - Zhiyuan Yao; Huiling Hu; Tao Wang; Xiaoguo Wang; Yulong Li; Xiaoming Sun; Sina Adl; Fangfang Yan; Yingjie Zhang; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

A new class of higher-order topological insulators that localize energy at arbitrary multiple sites - Yimeng Sun; Linjuan Wang; Huiling Duan; Jianxiang Wang (Science Bulletin, 2025)

MTHFD2 stabilizes LOX expression through RNA methylation modification to promote sepsis-induced acute kidney injury progression - Shudong Sun; Baoyi Han; Guohui Ren; Lei Fan; Junchao Sun; Huiling Li; Jiyi Huang (Human Cell, 2025)

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

Novel colorimetric-fluorescent dual-mode biosensing platform for detecting acetylcholinesterase and screening acetylcholinesterase inhibitors based on trimetallic nanozymes - Meie Zheng; Mingxing Liu; Fei Ma; Zichen Song; Hongda Zhu; Huiling Guo; Hongmei Sun (Chemical Engineering Journal, 2025)

HIG-2 promotes glioma stemness and radioresistance mediated by IGFBP2-rich microparticles in hypoxia - Ying Yang; Ting Sun; Xuefei Xue; Huiling Tan; Yanyan Li; Wei Yang (Apoptosis, 2025)

Global phylogeography and genomic characterization of Vibrio parahaemolyticus infections in Jilin province, China (2016–2022) - Jingying Zheng; Ben Shi; Jingyu Sun; Yang Pan; Yukun Ding; Xuening Shi; Jing Zhang; Huiling Zhang; Jingtong He; Kunlun Zhang; Jianyang Shi; Yang Bai; et al. (International Journal of Food Microbiology, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

Roles of boron in preventing cadmium uptake by Capsicum annuum root tips: Novel insights from ultrastructural investigation and single-cell RNA sequencing - Baifei Huang; Yingying Huang; Chuang Shen; Ling Fan; Huiling Fu; Zhilin Liu; Yingfang Sun; Bin Wu; Jirong Zhang; Junliang Xin (Science of The Total Environment, 2024)

Real-time monitoring of maize phenology with the VI-RGS composite index using time-series UAV remote sensing images and meteorological data - Ziheng Feng; Zhida Cheng; Lipeng Ren; Bowei Liu; Chengjian Zhang; Dan Zhao; Heguang Sun; Haikuan Feng; Huiling Long; Bo Xu; Hao Yang; Xiaoyu Song; et al. (Computers and Electronics in Agriculture, 2024)

La-doped O3-type layered oxide cathode with enhanced cycle stability for sodium-ion batteries - Lihua Feng; Yufan Xia; Jinze Guo; Huiling Liu; Youchen Hao; Ziqi Tian; Xin Xiao; Lijie Feng; Chujun Sun; Shunmian Qi; Kuoqin Li; Yong Li; et al. (Chemical Engineering Journal, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Response of aquatic ammonia-oxidizing archaea to thermal stratification and nutrient levels since the Last Glacial Maximum in the deep lake Fuxian, southwestern China - Pingbo Zheng; Huan Yang; Gordon Inglis; Caiming Shen; Hucai Zhang; Huiling Sun (Quaternary Science Reviews, 2024)

Aberrant Hippocampal Development in Early-onset Mental Disorders and Promising Interventions: Evidence from a Translational Study - Jingyu Yang; Huiling Guo; Aoling Cai; Junjie Zheng; Juan Liu; Yao Xiao; Sihua Ren; Dandan Sun; Jia Duan; Tongtong Zhao; Jingwei Tang; Xizhe Zhang; et al. (Neuroscience Bulletin, 2024)
Early-onset mental disorders are associated with disrupted neurodevelopmental processes during adolescence. The methylazoxymethanol acetate (MAM) animal model, in which disruption in neurodevelopmental processes is induced, mimics the abnormal neurodevelopment associated with early-onset mental disorders from an etiological perspective. We conducted longitudinal structural magnetic resonance imaging (MRI) scans during childhood, adolescence, and adulthood in MAM rats to identify specific brain regions and critical windows for intervention. Then, the effect of repetitive transcranial magnetic stimulation (rTMS) intervention on the target brain region during the critical window was investigated. In addition, the efficacy of this intervention paradigm was tested in a group of adolescent patients with early-onset mental disorders (diagnosed with major depressive disorder or bipolar disorder) to evaluate its clinical translational potential. The results demonstrated that, compared to the control group, the MAM rats exhibited significantly lower striatal volume from childhood to adulthood (all P <0.001). In contrast, the volume of the hippocampus did not show significant differences during childhood ( P >0.05) but was significantly lower than the control group from adolescence to adulthood (both P <0.001). Subsequently, rTMS was applied to the occipital cortex, which is anatomically connected to the hippocampus, in the MAM models during adolescence. The MAM-rTMS group showed a significant increase in hippocampal volume compared to the MAM-sham group ( P <0.01), while the volume of the striatum remained unchanged ( P >0.05). In the clinical trial, adolescents with early-onset mental disorders showed a significant increase in hippocampal volume after rTMS treatment compared to baseline ( P <0.01), and these volumetric changes were associated with improvement in depressive symptoms ( r = − 0.524, P = 0.018). These findings highlight the potential of targeting aberrant hippocampal development during adolescence as a viable intervention for early-onset mental disorders with neurodevelopmental etiology as well as the promise of rTMS as a therapeutic approach for mitigating aberrant neurodevelopmental processes and alleviating clinical symptoms.

Scientific Advances and Weather Services of the China Meteorological Administration’s National Forecasting Systems during the Beijing 2022 Winter Olympics - Guo Deng; Xueshun Shen; Jun Du; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Jiangkai Hu; Jianjie Wang; et al. (Advances in Atmospheric Sciences, 2024)

A novel competitive fluorescence colorimetric dual-mode immunosensor for detecting ochratoxin A based on the synergistically enhanced peroxidase-like activity of AuAg NCs-SPCN nanocomposite - Chenxi Ke; Yu Wu; Zichen Song; Meie Zheng; Hongda Zhu; Huiling Guo; Hongmei Sun; Mingxing Liu (Food Chemistry, 2024)

Mowing and nitrogen management guidelines for superior rice ratoon yields - Deqiang Qi; Yalong Chen; Matthew Tom Harrison; Ke Liu; Huiling He; Changli Ji; Kai Du; Jiaqi Wang; Yajun Sun; Guilong Yu; Ye Liu; Yafan Zhao; et al. (Field Crops Research, 2024)

High trophic level organisms and the complexity of soil micro-food webs at aggregate scale regulate carbon accumulation in cropland soils - Zhiyuan Yao; Chuanxiong Huang; Huiling Hu; Tao Wang; Yulong Li; Xiaoming Sun; Sina Adl; Bo Zhu (Agriculture, Ecosystems & Environment, 2024)

The Spatiotemporal Distribution Characteristics of Cloud Types and Phases in the Arctic Based on CloudSat and CALIPSO Cloud Classification Products - Yue Sun; Huiling Yang; Hui Xiao; Liang Feng; Wei Cheng; Libo Zhou; Weixi Shu; Jingzhe Sun (Advances in Atmospheric Sciences, 2024)

Metabolomic and transcriptomic integrated analysis revealed the decrease of monoterpenes accumulation in table grapes during long time low temperature storage - Huiling Wang; Xiaoyue Wang; Ailing Yan; Zhenhua Liu; Jiancheng Ren; Haiying Xu; Lei Sun (Food Research International, 2023)

Development of an ultrasensitive sandwich immunoassay for detecting small molecule semicarbazide - Shiwei Zhang; Ronghu Feng; Huiling Wu; Jiping Guo; Yingchun Zhou; Xintian Lai; Yanyan Sun; Yudong Shen; Bing Liu; Xingxing Yang; Bingzhi Wang (Food Chemistry, 2023)

Mapping research trends and identifying missing research gaps in green environment and public health: a bibliometric analysis for 2003–2021 - Huiling Wang; Fei Sun; Junming Su; Sanchir Bold; Mansoor Ahmed Koondhar (Environment, Development and Sustainability, 2023)

Influence of hydrological parameters on hydroxylated tetraether lipids in a deep Lake Fuxian, China: Implications for their use as environmental proxies - Pingbo Zheng; Huan Yang; Hucai Zhang; Caiming Shen; Huiling Sun (Science of The Total Environment, 2023)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

Novel electron donor boosting the electron supply capacity of hierarchical structure carbon nitride for efficient photocatalytic hydrogen peroxide production - Linlin Sun; Xiaoshuo Liu; Huiling Ji; Xunlei Ding; Nan Jiang; Jigang Wang (Chemical Engineering Journal, 2023)

Accumulative plastic strain of freezing–thawing subgrade clay under cyclic loading and its particle swarm optimisation–back-propagation-based prediction model - Yiqiang Sun; Shijie Zhou; Shangjiu Meng; Miao Wang; Huiling Bai (Cold Regions Science and Technology, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Cloud Microphysical Processes and Atmospheric Water Budget during the 20 July 2021 Extreme Precipitation Event in Zhengzhou, China - Weixi Shu; Danhong Fu; Hui Xiao; Huiling Yang; Yue Sun; Xueliang Guo; Yang Zhao; Jianfang Ding; Shujing Shen (Journal of Meteorological Research, 2023)

Material efficiency strategies across the industrial chain to secure indium availability for global carbon neutrality - Huiling Song; Chang Wang; Kun Sun; Hongjun Geng; Lyushui Zuo (Resources Policy, 2023)

Cell activity manipulation through optimizing piezoelectricity and polarization of diphenylalanine peptide nanotube-based nanocomposite - Huiling Guo; Dong-Min Lee; Pin Zhao; So-Hee Kim; Inah Hyun; Byung-Joon Park; Ju-Hyuck Lee; Huajun Sun; Sang-Woo Kim (Chemical Engineering Journal, 2023)

Combined organic-inorganic fertilization builds higher stability of soil and root microbial networks than exclusive mineral or organic fertilization - Luhua Yang; Renhua Sun; Jungai Li; Limei Zhai; Huiling Cui; Bingqian Fan; Hongyuan Wang; Hongbin Liu (Soil Ecology Letters, 2023)

Preparation and model construction of novel 2D nanocomposite of Zn-P-GCNN and its mechanisms of synergistic adsorption for Cu(II) and methylene blue - Meie Zheng; Fei Ma; Mingxing Liu; Mengjiao Li; Qingjie Yu; Hongda Zhu; Huiling Guo; Hongmei Sun (Journal of Cleaner Production, 2023)

Spherical activated carbons derived from resin-microspheres for the adsorption of acetic acid - Huiling Wu; Huangzhao Wei; Xu Yang; Chengyu Jin; Wenjing Sun; Kai Deng; Xin Rong; Gu Bin; Chenglin Sun (Journal of Environmental Chemical Engineering, 2023)

Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices - Zhuo Sun; Juan Lu; Xin Zhang; Xiangyu Shan; Qian Wu; Chao Li; Huiling Li; Shuning Yang; Li Tian (Food Chemistry, 2023)

Optimization on structure and operation parameters of biofilter for decentralized sewage treatment - Zhiheng Xia; Wenqian Cai; Jinsen Zhang; Wenzhuo Sun; Zhao Jiang; Yinghao Li; Ziding Ao; Huiling Chen; Guohua Liu; Lu Qi; Hongchen Wang (Environmental Research, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Abundant bacteria and fungi attached to airborne particulates in vegetable plastic greenhouses - Changliang Nie; Xueyun Geng; Huiling Ouyang; Lina Wang; Zongzhen Li; Mingyu Wang; Xiaomin Sun; Yan Wu; Yunhan Qin; Youxin Xu; Xu Tang; Jianmin Chen (Science of The Total Environment, 2023)

Colorless Electrochromic/Electrofluorochromic Dual-Functional Triphenylamine-Based Polyimides: Effect of a Tetraphenylethylene-Based π-Bridge on optoelectronic properties - Tiechen Yu; Patrick Theato; Hongyan Yao; Huiling Liu; Yizeng Di; Zhonghui Sun; Shaowei Guan (Chemical Engineering Journal, 2023)

Exosome-derived miR-200a promotes esophageal cancer cell proliferation and migration via the mediating Keap1 expression - Peng Li; Xianben Liu; Wenqun Xing; Huiling Qiu; Renling Li; Shilei Liu; Haibo Sun (Molecular and Cellular Biochemistry, 2022)

Preface to the Special Issue on Summer 2020: Record Rainfall in Asia — Mechanisms, Predictability and Impacts - Robin T. Clark; Xiquan Dong; Chang-Hoi Ho; Jianhua Sun; Huiling Yuan; Tetsuya Takemi (Advances in Atmospheric Sciences, 2021)

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Methods used for the measurement of blood-brain barrier integrity - Huixin Sun; Huiling Hu; Chuanjie Liu; Nannan Sun; Chaohui Duan (Metabolic Brain Disease, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Insights into the effects of Zn exposure on the fate of tylosin resistance genes and dynamics of microbial community during co-composting with tylosin fermentation dregs and swine manure - Bo Zhang; Qingbin Yuan; Meng meng Wang; Ruonan Sun; Huiling Liu; Peng Wang (Environmental Science and Pollution Research, 2021)

Immobilization of fluoride in the sediment of mine drainage stream using loess, Northwest China - Yueyue Li; Shengli Wang; Huiling Sun; Wen Huang; Zhongren Nan; Fei Zang; Yepu Li (Environmental Science and Pollution Research, 2020)

Comparison of Al18F- and 68Ga-labeled NOTA-PEG4-LLP2A for PET imaging of very late antigen-4 in melanoma - Yongkang Gai; Lujie Yuan; Lingyi Sun; Huiling Li; Mengting Li; Hanyi Fang; Bouhari Altine; Qingyao Liu; Yongxue Zhang; Dexing Zeng; Xiaoli Lan (JBIC Journal of Biological Inorganic Chemistry, 2020)

Assessment of source and health risk of metal(loid)s in indoor/outdoor dust of university dormitory in Lanzhou City, China - Lili Bao; Shengli Wang; Huiling Sun; Wen Huang; Guanxin Wang; Zhongren Nan (Environmental Science and Pollution Research, 2019)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Mid- to- late Holocene hydroclimatic changes on the Chinese Loess Plateau: evidence from n-alkanes from the sediments of Tianchi Lake - Huiling Sun; James Bendle; Osamu Seki; Aifeng Zhou (Journal of Paleolimnology, 2018)

Comparison of aerosol effects on simulated spring and summer hailstorm clouds - Huiling Yang; Hui Xiao; Chunwei Guo; Guang Wen; Qi Tang; Yue Sun (Advances in Atmospheric Sciences, 2017)

Characterization of the global transcriptome and microsatellite marker information for spotted halibut Verasper variegatus - Jianlong Ge; Siqing Chen; Changlin Liu; Li Bian; Huiling Sun; Jie Tan (Genes & Genomics, 2017)

Association of Serum Heavy Metals and Trace Element Concentrations with Reproductive Hormone Levels and Polycystic Ovary Syndrome in a Chinese Population - Guanchao Zheng; Lijun Wang; Zhizhun Guo; Lingbin Sun; Lingling Wang; Chonggang Wang; Zhenghong Zuo; Huiling Qiu (Biological Trace Element Research, 2015)

Mechanical stress induces neuroendocrine and immune responses of sea cucumber (Apostichopus japonicus) - Jie Tan; Fenghui Li; Huiling Sun; Fei Gao; Jingping Yan; Chunlei Gai; Aihua Chen; Qingyin Wang (Journal of Ocean University of China, 2015)

Parathyroid hormone-related protein overexpression protects goat mammary gland epithelial cells from calcium-sensing receptor activation-induced apoptosis - Hui Li; Yongsen Sun; Huiling Zheng; Lihui Li; Qian Yu; Xiaotong Yao (Molecular Biology Reports, 2015)

Changing intensity of human activity over the last 2,000 years recorded by the magnetic characteristics of sediments from Xingyun Lake, Yunnan, China - Duo Wu; Aifeng Zhou; Jianbao Liu; Xuemei Chen; Haitao Wei; Huiling Sun; Junqing Yu; Jan Bloemendal; Fahu Chen (Journal of Paleolimnology, 2015)

Bacterial diversity of gut content in sea cucumber (Apostichopus japonicus) and its habitat surface sediment - Fei Gao; Jie Tan; Huiling Sun; Jingping Yan (Journal of Ocean University of China, 2014)

Th17 cell expansion in gastric cancer may contribute to cancer development and metastasis - Zhaoliang Su; Yingkun Sun; Haitao Zhu; Yueqin Liu; Xin Lin; Huiling Shen; Jianguo Chen; Wenlin Xu; Huaxi Xu (Immunologic Research, 2014)

Human SMAD4 is phosphorylated at Thr9 and Ser138 by interacting with NLK - Yan Shi; Kan Ye; Huiling Wu; Yixing Sun; Huili Shi; Keke Huo (Molecular and Cellular Biochemistry, 2010)